Application of a wax deposition model in oil production pipelines - Chaves Guerrero, Arlex; Bautista Parada, Diego Fernando; Fuentes Díaz, David Alfredo; Gauthier Maradei, Paola (CT&F - Ciencia, Tecnología y Futuro, 2015)
This work is aimed to study the wax deposition process on the internal surface of oil production pipelines and the influence of parameters such as flow rate and pipe wall temperature on the deposit thickness for a light crude oil with high paraffinic content considering three different temperature boundary conditions on the pipe wall; two of which assumed a profile temperature on the boundary, fact that has not been considered in previous works, and the third a constant value. The analysis was conducted assuming pseudo steady conditions on the fluid phase. The finite differences method was applied to solve the differential equation system and the solution was implemented numerically using the C++ programming language. The model was validated with the experimental results reported by Singh et al. (2000) and subsequently used to simulate the growth of the paraffin deposits as a function of flow rate and pipe temperature. The results showed that increased flow rates reduce the maximum deposit thickness, as it spreads on a longer distance in the pipe when considering a constant wall temperature or the axial thermal gradient with a positive slope, and the opposite effect is observed when considering the axial thermal gradient with a negative slope.